2016
DOI: 10.14737/journal.aavs/2016/4.4.174.177
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Hepatic Lesions and Incriminating Pathogens in Rural Scavenger Chickens in Maiduguri, North-Eastern Nigeria

Abstract: | The survey of hepatic lesions in rural scavenger chickens was carried out in Maiduguri live chicken market. A total of 100 liver tissue and swab samples were collected for histopathological and bacteriological analysis. The result obtained revealed that 20 % of the liver were enlarged, 57% have variable degree of hemorrhage while 77% were pale. In addition, friability and fibrin deposits were observed in 3% and 5% of the liver respectively. Similarly, histopathologic lesions observed, includes varying degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The poultry industry has assumed greater importance in improving employment opportunities and animal food production in Nigeria [19][20][21]. Earlier reports showed that poultry production accounts for about 36.5% of sources of protein in Nigeria [22,23]. However, the viability and growth of this sector is hampered by diseases which have consequently resulted in reduced output in terms of production [12].…”
Section: Introductionmentioning
confidence: 99%
“…The poultry industry has assumed greater importance in improving employment opportunities and animal food production in Nigeria [19][20][21]. Earlier reports showed that poultry production accounts for about 36.5% of sources of protein in Nigeria [22,23]. However, the viability and growth of this sector is hampered by diseases which have consequently resulted in reduced output in terms of production [12].…”
Section: Introductionmentioning
confidence: 99%
“…P oultry production contributes substantially to socio-economic development of many developing countries of the world (Gambo et al, 2016;Henning et al, 2009).To many households, it serves as an important sources of income and protein. However, the major setbacks associated with poultry production in many rural and urban settlements is poor management and diseases such as Newcastle disease (Henning et al, 2009;Mapiye et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria has the largest poultry population in Africa (Abubakar et al, 2007) with an estimated poultry population of about 130 -150 million chickens (Gambo et al, 2016;Pagani et al, 2008). The high incidence of infectious diseases have impacted negatively on the growth of the poultry industry (Oladeebo and Ambe-Lamidi, 2007) resulting in a significant decrease in their performance and survival rate.…”
Section: Introductionmentioning
confidence: 99%